2014
DOI: 10.1186/1471-2407-14-915
|View full text |Cite
|
Sign up to set email alerts
|

Case series discussion of cardiac and vascular events following carfilzomib treatment: possible mechanism, screening, and monitoring

Abstract: BackgroundCarfilzomib is a selective proteasome inhibitor approved in the United States in 2012 for the treatment of relapsed and refractory multiple myeloma. Although cardiopulmonary and vascular events have been reported infrequently, they can be potentially serious complications, and their incidence and pathophysiology following carfilzomib treatment remain poorly characterized in a real-world patient population.MethodsWe retrospectively reviewed the records of 67 patients with relapsed and/or refractory mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 42 publications
3
78
0
1
Order By: Relevance
“…Careful clinical volume status assessment may be a useful measure to proactively manage patients at risk for developing heart failure. Increasing evidence suggests a possible effect of proteasome inhibition on vascular endothelium, [34][35][36][37] rather than cardiac myocytes. Therefore, vascular impact biomarkers should be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Careful clinical volume status assessment may be a useful measure to proactively manage patients at risk for developing heart failure. Increasing evidence suggests a possible effect of proteasome inhibition on vascular endothelium, [34][35][36][37] rather than cardiac myocytes. Therefore, vascular impact biomarkers should be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the rates of peripheral neuropathy are lower with carfilzomib, a few patients have developed cardiovascular complications, including hypertension and heart failure with decreased left ventricular ejection fraction 46 . Endothelial dysfunction has been proposed to occur after carfilzomib administration through inhibition of endothelial nitric oxide synthase activity 52 . An echocardiography assessment is recommended for all patients before starting carfilzomib treatment, though utility of this evaluation in predicting those at risk for cardiac events has not been proven, and additional studies are needed in this area.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in the ENDEAVOR study, the incidence of hypertension was reported to be higher in the Kd group compared with the Vd group [60]. Intervention with antihypertensive medications and the cautious use of diuretics have been suggested as beneficial symptomatic management strategies in patients reporting hypertension after treatment with carfilzomib [72].…”
Section: Safetymentioning
confidence: 95%
“…Cardiac events have been reported to be associated with proteasome inhibition and are hypothesized to be a class effect for these agents [71][72][73]. Cardiac failure was reported in 7% of patients in the Phase II studies, although it should also be noted that 74% of patients had a medical history of cardiovascular disease [64].…”
Section: Safetymentioning
confidence: 98%